(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article it is investigated, using the megatext of Hryhir Tiutiunnyk some specific features of the character of the writer. Detailed analysis of properties of char-acter, which were inherent by the writer. Analyzed the memories of letters of the rela-tives to underscore his personality traits. Studied the epistolary of prosaist as one of the source of the expression of psyhoautobiographical characteristics of the writer.